L-lysine potentiates aminoglycosides against Acinetobacter baumannii via regulation of proton motive force and antibiotics uptake - Wanyan Deng; Tiwei Fu; Zhen Zhang; Xiao Jiang; Jianping Xie; Hang Sun; Peng Hu; Hong Ren; Peifu Zhou; Qi Liu; Quanxin Long (Emerging Microbes and Infections)
Acinetobacter baumannii, a Gram-negative opportunistic pathogen, is a leading cause of hospital- and community-acquired infections. Acinetobacter baumannii can rapidly acquire diverse resistance mechanisms and undergo genetic modifications that confer resistance and persistence to all currently used clinical antibiotics. In this study, we found exogenous L-lysine sensitizes Acinetobacter baumannii, other Gram-negative bacteria (Escherichia coli and Klebsiella pneumoniae) and a Gram-positive bacterium (Mycobacterium smegmatis) to aminoglycosides. Importantly, the combination of L-lysine with aminoglycosides killed clinically isolated multidrug-resistant Acinetobacter baumannii and persister cells. The exogenous L-lysine can increase proton motive force via transmembrane chemical gradient, resulting in aminoglycoside acumination that further accounts for reactive oxygen species production. The combination of L-lysine and antibiotics highlights a promising strategy against bacterial infection.